Solution structure of the strawberry allergen Fra a 1. Issue 6 (5th October 2012) - Seutter von Loetzen, Christian; Schweimer, Kristian; Schwab, Wilfried; Rösch, Paul; Hartl-Spiegelhauer, Olivia
Abstract : The PR10 family protein Fra a 1E from strawberry ( Fragaria x ananassa ) is down-regulated in white strawberry mutants, and transient RNAi (RNA interference)-mediated silencing experiments confirmed that Fra a 1 is involved in fruit pigment synthesis. In the present study, we determined the solution structure of Fra a 1E. The protein fold is identical with that of other members of the PR10 protein family and consists of a seven-stranded antiparallel β-sheet, two short V-shaped α-helices and a long C-terminal α-helix that encompass a hydrophobic pocket. Whereas Fra a 1E contains the glycine-rich loop that is highly conserved throughout the protein family, the volume of the hydrophobic pocket and the size of its entrance are much larger than expected. The three-dimensional structure may shed some light on its physiological function and may help to further understand the role of PR10 proteins in plants.